Peran Museum Rumah Garuda dalam Meningkatkan Pembelajaran Identitas Nasional - Octina, Rooseline Linda; Permatasari, Rr. Yudiswara Ayu (Journal of Civic Education, 2025)
This article explores the strategic role of the Rumah Garuda Museum in promoting national identity education. National identity serves as a crucial foundation in fostering historical awareness, civic engagement, and social solidarity. Using a qualitative approach involving interviews, observations, and literature analysis, this study examines the learning model applied at the Rumah Garuda Museum. The findings reveal that the museum adopts a constructivist learning approach, emphasizing active visitor participation and reflective dialogue. Museum spaces are designed to encourage personal interpretation and meaning-making, allowing visitors to build individual understandings of national identity through curated historical narratives and exhibits. The museum also plays a role in fostering civic knowledge, civic skills, and civic culture. Civic knowledge is strengthened through exposure to historically significant collections, while civic skills are developed via critical discussions and interactive learning. Civic culture is nurtured by participatory experiences that build awareness of shared values, cultural diversity, and collective responsibility. The study concludes that the Rumah Garuda Museum effectively serves as both a reflective historical space and an educational platform that shapes informed, critical, and culturally rooted citizens. It highlights the importance of integrating civic education dimensions into informal learning spaces to support democratic citizenship in the digital era.